Utilizing Sustainable Recycled Thermoplastic Polymers in 3D Printing Filament - Hussein, Bashar Dheyaa; Sadiq, Ghanim Sh. (Al-Nahrain Journal for Engineering Sciences, 2025)
Over the last several years, additive manufacturing (AM), sometimes known as "3D printing", has seen remarkable expansion due to mechatronics and materials science advancements. Fused filament deposition (FDM) production is the predominant technology in additive manufacturing (AM) because of its cost-effectiveness in operational and material expenses. Nevertheless, the materials often used for this technique are pristine thermoplastics. Unsuccessful printing and throwaway prototypes generate a significant quantity of trash. Utilizing green and sustainable products is crucial to minimize the environmental effects. Recycled, bio-based, and mixed recycled materials provide a promising solution for 3D printing. The absence of comprehension about the interlayer adhesion process and material degradation in FDM printing has presented a significant obstacle for these environmentally friendly materials. This study comprehensively examines many materials used for FDM three-dimensional printing filaments, including recycled, bio-based, and mixed materials. The merits and drawbacks of thermoplastics and their composites were deliberated over. This evaluation is a comprehensive guide for engineers and researchers in selecting appropriate materials for three-dimensional printing. Three-dimensional printed objects have worse mechanical characteristics in comparison to injection molded materials.